2005
DOI: 10.1016/j.febslet.2005.11.072
|View full text |Cite
|
Sign up to set email alerts
|

Transformation‐associated gene regulation by ATF6α during hepatocarcinogenesis

Abstract: We have previously reported that the endoplasmic reticulum (ER) stress-regulated transmembrane transcription factor 6 a (ATF6a) is implicated in the pathogenesis of hepatocellular carcinomas (HCCs). In order to further identify genes that are regulated by ATF6a, the global gene expression profiles of the ATF6a-transfected and untransfected HCC cell line, HLF, were analyzed. These results were then compared with the differential gene expression patterns of poorly differentiated HCC and control non-tumorous live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 19 publications
1
39
0
Order By: Relevance
“…Expression of ATA1, ATA2, and LAT1 mRNAs in five normal livers (normal), 25 HCCs and matched non-cancerous liver tissues. Total RNA extracts from these tissues were subjected to QRT-PCR as described (16). The relative mRNA expression levels were then calculated by normalizing with a ß 2 -microglobulin control.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of ATA1, ATA2, and LAT1 mRNAs in five normal livers (normal), 25 HCCs and matched non-cancerous liver tissues. Total RNA extracts from these tissues were subjected to QRT-PCR as described (16). The relative mRNA expression levels were then calculated by normalizing with a ß 2 -microglobulin control.…”
Section: Discussionmentioning
confidence: 99%
“…So far, it has been demonstrated that ATF6 is required for the adaptation of dormant squamous carcinoma cells to nutritional stresses and in vivo microenvironment through the up-regulation of RHEB and activation of mTOR signaling (56). Moreover, as shown in the hepatocellular carcinoma model, ATF6 may be involved in the regulation of cell proliferation (57) or in the sensitivity to chemotherapy in leukemia cells (58). Data also suggest ATF6 contribution to cancer progression by shaping tumor microenvironment (59) as well as in the induction of the senescent phenotype (60).…”
Section: Atf6mentioning
confidence: 98%
“…ATF6α transactivates target genes that include ubiquitin-conjugating enzyme E2C (UBE2C) and CDKN3, which promote tumorigenesis (Arai et al 2006). Polymorphisms in ATF6a are associated with increased expression and hepatocellular carcinoma ).…”
Section: Atf6αmentioning
confidence: 99%